Comparing simulation results and experimental measurements of electroluminescence phenomenon in dielectric materials - Ariffin A.M.; Tajudin N.M.; Sulaiman S.; Thayoob Y.H.Md.; Lewin P.L. (2023)
Under continuous application of high electrical stresses, the insulation system of an underground power cable is subjected to long-term degradation that can eventually cause premature breakdown of the cable. This is as a result of electronic charges being injected into the dielectric material when intense electric field is applied. These charges will then interact with polymer molecules; causing even more charges to accumulate within the vicinity of the material and thus further deterioration. The interaction of the charges can lead to the dissipation of energy in the form of photons; a process known as electroluminescence (EL). In addition to space charge probing, the measurement of EL has becoming increasingly prominent in understanding the mechanisms that contribute to the early electrical ageing of an insulating material. This paper attempts to simulate EL behaviour based on the underlying hypotheses of charge injection and bipolar recombination processes that take place within a polymer. A detailed comparison between the computation results and the experimental measurements carried out by different researchers will be discussed in order to evaluate the mechanisms responsible for this phenomenon. 2010 IEEE.